METODE DISKUSI DALAM PEMBELAJARAN: ANALISIS KUALITAS HADITS - Maslani Maslani; Kiki Miftahul Hakiki; Habibah Nur Azizah; Miftah Falah Udwi Syarfiah; Zahra Nur Azizah (Jurnal Bilqolam Pendidikan Islam, 2025)
This article discusses the application of discussion methods in learning, especially in the context of Islamic education, and analyzes the quality and quantity of related hadiths. Discussion methods as a learning strategy are considered effective in encouraging active student participation, fostering a tradition of critical thinking, and creating a dynamic learning atmosphere. The study of hadith in this article is carried out through the takhrij approach and sanad analysis, with an emphasis on the quality of the narrators and the continuity of their sanads. One of the hadiths analyzed is the history of Imam Muslim No. 9, which discusses faith, Islam, and destiny. The results of the study show that the sanad of the hadith is muttashil and all of its narrators have a tsiqah reputation, so that the hadith can be categorized as a sahih hadith. Thus, the discussion method is not only relevant in modern learning, but also has a strong basis in the classical Islamic treasury.